USING INNOVATIVE TECHNOLOGIES IN TEACHING ENGLISH - Mahliyo Ilyasova,; Liliya Iskandarova, (JOURNAL OF NEW CENTURY INNOVATIONS, 2024)
The application of innovative technologies in teaching English plays a crucial role in making the educational process more effective and engaging. Today, tools such as e-learning platforms, mobile applications, virtual reality, and games facilitate language learning for students. These technologies enhance interactivity, boost student motivation, and create opportunities for individualized instruction. Through innovative approaches, students’ ability to apply the language in practice is developed, making the teaching process more effective.